Black Readings of Exodus - Trimm, Charlie (Currents in biblical research, 2024)
Most academic study of the Hebrew Bible/Old Testament in North America has been done from a White European or North American perspective. Post-graduate schools have predominantly required students to read works written by White authors, and the vast majority of professors are White. However, the Hebrew Bible/Old Testament also has a long history of interpretation by non-White and Majority World thinkers, and their contributions need to be more widely acknowledged and employed in studying the Hebrew Bible/Old Testament. This article surveys the contributions of Black Hebrew Bible/Old Testament scholars on the book of Exodus. Black scholars employ a variety of methods and approaches as they engage with the biblical text. We consider these approaches by category, beginning with textual criticism and translation before exploring works that focus on Africa in the Bible, those that draw on African or African American context, and those that highlight issues of gender or the perspectives of liberation theology. We conclude with those employing multi-faceted or integrative approaches.